The Effects of a Magic Intervention Program on Cognitive Function and Neurocognitive Performance in Elderly Individuals With Mild Cognitive Impairment - Lee, Kuan-Ting; Wang, Wei-Li; Lin, Wen-Chin; Yang, Yi-Ching; Tsai, Chia-Liang (Frontiers in Aging Neuroscience, 2022)
Objectives Cognitive training is one of the management options for elderly individuals who suffer from mild cognitive impairment (MCI) and an effective way to improve executive function. This study aimed to evaluate the effectiveness of a magic intervention program as a method of cognitive training in improving cognitive function and neurocognitive performance in this group. Methods Twenty-four participants aged 60–80 years with MCI were recruited and randomly assigned to a magic intervention group or a control group. The magic intervention group received a 6-week magic intervention program. The primary endpoints were the scores for the cognitive assessment tests [e.g., Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA)] for general cognitive function. The secondary endpoints were the behavioral [e.g., accuracy and reaction times] and the electroencephalographic [e.g., event-related potential (ERP) P3 amplitudes] performance during the Flanker task to assess attention and inhibitory control. All variables were measured before and after the magic intervention. Results The results showed that the 6-week magic intervention significantly improved the MoCA scores in the cognitive assessment tests although no significant pre-post intervention difference was observed in the MMSE scores. In terms of neurocognitive performance, the magic intervention had significantly positive effects on the accuracy, reaction times, and P3 amplitudes when performing the Flanker task. Conclusion The results of the present study showed that the 6-week magic intervention had beneficial effects on the cognitive and electrophysiological performance in the elderly subjects with MCI. For such a group, lifestyle intervention programs that encourage participation such as the magic practice and performance may be a viable suggestion to prevent the progression of MCI to Alzheimer’s disease.